Bad and Good Faith of the Applicant in the Restitution Process: The Case-Law of the ECtHR - Bruskina, Nika (Teisė, 2018)
[full article, abstract in Lithuanian; only abstract in English]The Article examines the case-law of the ECtHR related to the good or bad faith of the applicant in the context of the restoration of ownership rights to the property nationalized in the past.
Keywords: none